Factors Influencing Tax Knowledge and Tax Sanctions on Taxpayer Awareness Among Coffee Farmers - Mariana Lili Milianti; Herlambang Pudjo Santosa (Journal of Creative Power and Ambition (JCPA), 2026)
Public tax awareness is an important factor in supporting the sustainability of state revenue, especially in the agrarian sector. This study aims to analyze the effect of understanding tax regulations and sanction policies on the level of taxpayer awareness among coffee farmers in Ngada Regency. An associative quantitative approach was used in this study, with primary data collected through structured questionnaires distributed to 100 respondents. Data analysis was conducted using multiple linear regression to examine the relationships between variables. The results show that understanding tax regulations has a positive and significant effect on taxpayer awareness. Tax sanction policies are also proven to have a significant influence in encouraging compliance. Simultaneously, both variables contribute 39% to the formation of tax awareness. These findings indicate that increasing inclusive tax education and consistent enforcement of sanctions are important factors in improving tax compliance in the plantation sector.